Revolutionizing Leadership Training with Virtual Reality: Preparing Indonesia's Next-Gen Workforce through Startup Case Studies - Dea Amirotul Ahlam; Untung Lasiyono; Zahwa Noveliza Nur Safitri (Proceeding International Conference on Digital Education and Social Science, 2024)
Along with the rapid development of the digital era, Indonesia needs leaders who are able to adapt and innovate to strengthen its competitiveness on the global stage. Unfortunately, traditional leadership training methods are now considered inadequate to meet the increasingly complex demands. This research focuses on exploring the use of Virtual Reality (VR) technology in leadership training by analyzing literature from various sources to identify the potential, benefits, and challenges that exist in the implementation of VR in this training. Using the library research method, this study examines in depth the literature's views on the effectiveness of VR as a training medium that offers a realistic and immersive simulated environment experience. The results showed that VR can assist trainees in honing critical leadership skills, such as sound decision-making, effective communication, and crisis management, under safe yet realistic conditions. Based on these findings, VR integration is recommended as one of the main approaches in leadership training programs in Indonesia to equip aspiring leaders with relevant skills in the digital era.